Psychoeducational Intervention To Enhance Emotional Regulation Skills Among High School Students Facing University Entrance Examinations - Irba Chalisha Amaly; Cahyaning Suryaningrum; Latipun (Jurnal Pengabdian Masyarakat Sabangka, 2026)
Grade XII students often experience emotional pressure when preparing for university entrance examinations, which may trigger anxiety, negative thoughts, and difficulties in managing emotions. This community service program aimed to improve students’ knowledge and emotion regulation skills through psychoeducation based on creative-expressive activities. A pre-experimental method with a one-group pre-test–post-test design was employed involving 10 Grade XII students in District X, Central Kalimantan. The program was conducted in four sessions combining material delivery, discussion, emotional reflection, and creative activities. The results showed a significant improvement in students’ knowledge and emotion regulation skills after participating in the psychoeducation program. These findings indicate that psychoeducation based on creative-expressive activities has the potential to serve as an effective preventive intervention to help students regulate their emotions more adaptively when facing the pressures and demands of university entrance examination preparation, while also strengthening their psychological readiness to undergo the challenging higher education selection process.